2022
DOI: 10.15366/reice2023.21.1.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Teachers’ Work Engagement: The Case of Private School Teachers in Jakarta Metropolitan, Indonesia

Abstract: Previous studies found the phenomenon that the level of work engagement (WE) is deficient in various parts of the world, including in educational organizations. This research aims to analyze how perceived organizational support (POS) and servant leadership (SL) in schools affect teachers' WE. Additionally, this research also aims to examine the mediating role of meaningful work (MW). This research was conducted with a cross-sectional study design with the PLS-SEM method. The research data was obtained through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Los directivos pueden desempeñar un papel importante en la creación de un trabajo significativo en las escuelas mediante la comunicación de metas, valores y contribuciones a la sociedad. Además, pueden mostrar a los docentes cómo sus objetivos profesionales se alinean con sus valores y creencias fundamentales sobre la importante labor que realizan (Tan, 2022;Imran, 2020;Sudibjo y Riantini, 2023).…”
Section: Resultsunclassified
“…Los directivos pueden desempeñar un papel importante en la creación de un trabajo significativo en las escuelas mediante la comunicación de metas, valores y contribuciones a la sociedad. Además, pueden mostrar a los docentes cómo sus objetivos profesionales se alinean con sus valores y creencias fundamentales sobre la importante labor que realizan (Tan, 2022;Imran, 2020;Sudibjo y Riantini, 2023).…”
Section: Resultsunclassified
“…Prior research has identified a prevalent deficiency in work engagement levels across different regions worldwide, including within educational environments (Sudibjo & Riantini, 2023). Consequently, further investigation is warranted to gain a deeper comprehension of this phenomenon (Cacciamani et al, 2022).…”
Section: Suggested Citationmentioning
confidence: 99%
“…As a notion best seen in positive psychology, teachers’ psychological wellbeing is described as their assessment and satisfaction with their personal fulfillment, wellness, and career [ 33 ]. Numerous research has found that an individual’s level of well-being has a considerable impact on both their psychological condition and their educational practices [ 9 , 12 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%